PENGARUH MOTIVASI, KOMPETENSI, DAN KOMPENSASI TERHADAP KINERJA PEGAWAI KPP PRATAMA BANTUL - Sadewo, Bambang; Assery, Syeh (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This study aims to analyze the effect of motivation, competency and compensation on the performance of the Primary Tax Office of Bantul Pratama employees partially and simultaneously. The method used in this study is a quantitative method, where data collection uses a questionnaire. The sample in this study amounted to 35 employees consisting of Account Representatives and Functional Tax Auditors from a total population of 94 employees. The validity test which shows the statements in this study are valid, while the reliability test using Cronbach's Alpha is stated to be reliable. This study uses multiple linear regression analysis. The results of the analysis show that each of the variables, namely motivation, competence, and compensation partially have a positive and significant effect on performance, as well as these three variables motivation, competence, and compensation together have a significant and influence on the Performance of KPP Pratama Bantul Employees. The coefficient of determination obtained in this study is 0.747, meaning that the performance variable is influenced by motivation, competence and compensation of 74.70% so that the remaining 25.30% is influenced by other variables.